Convergent synthesis of 1 → 3 C-branched polyamide dendrons - Brettreich, Michael; Hirsch, Andreas (Synlett, 1998)
A convergent synthesis of 1 → 3 C-branched polyamide dendrons was developed providing a facile access to defined monodisperse dendritic building blocks.